„Opinia publică”, regia Theodor-Cristian Popescu - Blaga, Raluca (Symbolon, 2020)
“The Public Opinion”, directed by Theodor-Cristian Popescu Twenty years after the fall of the communist regime, the theater director Theodor-Cristian Popescu theatrically assumes, as he states in his own words, a small provocative gesture: staging in October 2010, at Radu Stanca National Theatre from Sibiu, Aurel Baranga's play, “The Public Opinion”. Ingrained with specific communist dramaturgical flavours, in Theodor-Cristian Popescu's stage reading, Baranga's play takes the properties of a document. Therefore, the director's artistic endeavour, through the theatrical means that it uses, takes the form of a scenic essay. The present lecture will follow precisely those theatrical devices that constructed the performance. Thirty years after the fall of the communist regime, through this lecture, the director's small provocative gesture receives an answer via an analytical evaluation.